A Human Classification System for Biometric Parameters - Volner, R.; Boreš, P. (Elektronika ir Elektrotechnika, 2005)
The definition of task and events managed by the core module allows that the system can be adapted, changing the how the system works or adding new modules. The use of a classification module allows the human supervision contributing with greater reliability. Use of biometrics in increasing everyday, as security concerns do. The purpose of biometric systems is finding the identity of the user comparing his biometric data with the one previously stored. The author proposes in this paper a new architecture for an authentication system. In this paper we are going to use the drawings that form the characteristics of the hand palm, as are fold – commonly called lines of the hand, cracks, scars and even fold of the fingers for verify and identify to person. Ill. 9, bibl. 4 (in English; summaries in Lithuanian, English and Russian).